Agrobacterium tumefaciens-mediated transformation of Jatropha curcas L. with a polyhydroxyalkanoate gene (phaC) - Chesara Novatiano; Adi Pancoro; Erly Marwani (Indonesian Journal of Biotechnology, 2017)
Polyhydroxybutyrate is a component of bioplastics that is synthesized under the control of enzymes encoded by pha multigenes. The genes are naturally present in Ralstonia eutropha. However, the production of bioplastics in bacteria is inefficient because the bacterial biomass is relatively small compared with plants or fungi. As such, engineering techniques have been developed that enable pha genes to be inserted into plant biomass, and then be expressed in the biomass of the plant to produce polyhydroxybutyrate. The objectives of this study were to transform the tissue of Jatropha curcas using the phaC gene (a pha gene), to regenerate the transformed plant, and to confirm the presence of the inserted genes with PCR. The genetic transformation of J. curcas was mediated by Agrobacterium tumefaciens strain GV3101 containing pARTC by dipping the cotyledon tissue of J. curcas in a suspension of the bacterium for 30 min, followed by cocultivation for 3 d on Murashige and Skoog (MS) medium. The tissue was then placed on a selection medium, i.e. MS medium containing 13.3 µM BAP and 0.05 µM IBA with the addition of 20 mg/L kanamycin. The results showed that 12.35% of the tissue survived and regenerated into a shoot after 1–2 months. Molecular analysis of the transformed tissue was performed using phaC and nptII primers, in order to detect the presence of the phaC and nptII genes. Specific bands were detected at 659 bp and 700 bp, corresponding to the nptII primer and phaC primer, respectively.